THE PREVALENCE OF MISMANAGED TRAUMA IN DHQ TEACHING HOSPITAL ABBOTTABAD - Shah, Ali Asghar; Ahmed, Nazir; Ahmed, Waqar (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT A prospective study was conducted to determine the prevalence of mismanaged trauma from Jan, 1990 to December, 1990. One Thousand and Fifty patients were admitted in Orthopaedics Department during the period out of which 665 patients came in with trauma, 210 of whom were with complications of mismanagement. 251 patients (37.74%) reported after one week of the injury and 278 (41.8%) came after receiving treatment from one or more bone setters. The common complications of mismanagement were malunion, unreduced dislocations, contractures, gangrene and infections.